THE LEGAL STATUS OF QADHA SALAT: COMPARATIVE PERSPECTIVES OF AL-WASHLIYAH AND MUHAMMADIYAH SCHOLARS IN ADDRESSING MODERN CHALLENGES - Zakaria, Muhammad; Rasiqah, Fildza; Marpaung, Ariping; Nasution, Julaika; Mawaddah, Nadiyah (Al-Risalah, 2024)
This study explores the differing perspectives of Al-Washliyah and Muhammadiyah scholars on the permissibility of qadha salat, particularly in the context of modern challenges such as traffic congestion. The purpose of this research is to compare the legal reasoning and methodologies of these two prominent Islamic organizations in addressing contemporary issues related to qadha salat, while examining their adherence to traditional jurisprudential principles. The methodology employed is a qualitative comparative analysis, drawing from primary sources such as fatwas and official statements issued by Al-Washliyah and Muhammadiyah, as well as secondary literature on Islamic jurisprudence. Data collection involved document analysis and thematic categorization of legal opinions, supported by a critical review of relevant Qur’anic verses, Hadith, and classical fiqh literature. The results reveal significant differences in interpretation: Al-Washliyah allows qadha salat under specific conditions aligned with the Syafi'i school, emphasizing situational factors like physical inability, whereas Muhammadiyah rejects qadha salat for traffic-related delays, citing the absence of textual evidence in the Qur'an and Hadith. These findings highlight the dynamic interplay between traditional jurisprudence and contextual ijtihad. The originality of this research lies in its focused examination of qadha salat through the lens of two influential organizations, contributing to the broader discourse on adapting Islamic law to modern contexts. The implications of this study are significant for scholars and practitioners of Islamic law, as it underscores the importance of contextual ijtihad in addressing contemporary issues while maintaining fidelity to foundational texts. This work offers a nuanced understanding for Muslim communities navigating similar dilemmas in their daily lives.